A-site-deficiency effect on critical behavior in the Pr0.6Sr0.4MnO3 compound. Issue 40 (23rd September 2015) - Elleuch, F.; Bekri, M.; Hussein, M.; Triki, M.; Dhahri, E.; Hlil, E. K.; Bessais, L.
Abstract : We present the effect of vacancy in Pr0.6 Sr0.4 MnO3 via dc magnetisation measurements. Abstract : We present the effect of vacancy in Pr0.6 Sr0.4 MnO3 via dc magnetisation measurements. Using various techniques such as modified Arrott plots, the Kouvel–Fisher method, and Widom scaling relationship the values of T C (ferromagnetic transition temperature), as well as the β, γ and δ (critical exponents) are estimated. Critical exponents for the stoichiometric sample and the strontium deficient sample match well with those predicted for the tricritical mean field model. The vacancy in Pr0.5 □0.1 Sr0.4 MnO3 changes the universal class. The estimated critical exponents of the praseodymium deficient sample are close to those found out by the 3D-Ising model.